2016
DOI: 10.3758/s13421-016-0609-8
|View full text |Cite
|
Sign up to set email alerts
|

Phonological similarity in working memory span tasks

Abstract: In a series of four experiments, we explored what conditions are sufficient to produce a phonological similarity facilitation effect in working memory span tasks. By using the same set of memoranda, but differing the secondary-task requirements across experiments, we showed that a phonological similarity facilitation effect is dependent upon the semantic relationship between the memoranda and the secondary-task stimuli, and is robust to changes in the representation, ordering, and pool size of the secondary-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In order to avoid word length effect, all words used in this study were bi-syllabic (i.e., matching for word length). Since this study involves the AWM, it was important to consider the phonological similarity effect as words that sound almost similar were found to be harder to be recalled than those which sound distinctly different [21]. In order to avoid the phonological similarity effect, each word sequence consisted of dissimilar items (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In order to avoid word length effect, all words used in this study were bi-syllabic (i.e., matching for word length). Since this study involves the AWM, it was important to consider the phonological similarity effect as words that sound almost similar were found to be harder to be recalled than those which sound distinctly different [21]. In order to avoid the phonological similarity effect, each word sequence consisted of dissimilar items (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the predictive power of trait WMC using OSPAN or RSPAN may bring dissociations in the effects observed. In fact, previous research has found that because the OSPAN and RSPAN have different processing components (i.e., solving math problems for accuracy in OSPAN and reading sentences for accuracy in RSPAN), could cause the tasks to dissociate in their consistency for predicting performance on different outcomes (see Oberauer, 2009;Chow et al, 2016;Macnamara et al, 2011;Holden et al, 2020). However, this interpretation is speculative but worth further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…The speculation that WM has cue-dependent retrieval sub-process was supported by experiments setting sentences in RST (Schroeder, Copeland, & Bies-Hernandez, 2012; Towse et al, 2008; Towse, Hitch, Horton, & Harvey, 2010), phonological similarity (Chow, Macnamara, & Conway, 2016; Copeland & Radvansky, 2001; Macnamara, Moore, & Conway, 2011), and semantic category (Liesefeld, Hoffmann, & Wentura, 2016) as cues. Based on Unsworth and Engle’s WM model, we assumed that contextual information should work as a retrieval cue (e.g., Unsworth & Engle, 2007a).…”
Section: Overview Of the Current Studymentioning
confidence: 99%